UJI PERTUMBUHAN DAN PRODUKSI TIGA VARIETAS TANAMAN BUNCIS (Phaseolus vulgaris L.) DENGAN APLIKASI PUPUK GUANO - Farida (Jurnal Magrobis, 2022)
The examine production three plant variety buncis (Phaseolus vulgaris L.) with using guano fertilizer. The research was conducted between December 2021 until April 2022. The aim of this research was to determinethe most variety superior has growth with using guano fertilizer. Method which used in this research was split random complete (SRC) with 3 variety treatment and 3 guano fertilizer. Variety treatment are V1 = Lebat variety, V2 = Perkasa variety, V3 = Bayu variety. Guano treatment are = 10 ton/ha, = 15 ton/ha, = 20 ton/ha. The results showed that the variety treatment had a significant effect on plant length treatment at 4 WAP, pod weight per plot and bean plant productivity. Bayu (V3) variety produced the best variety because it produced 46.56 cm long chickpea plants aged 4 WAP, pod weight per plants of 32.51 grams and bean productivity of 2.43 tons/ha. The guano treatment showed a significant effect on the parameters of plant length at 2, 4 and 6 WAP but had no significant effect on the parameters of pod weight and bean productivity. Treatment G3 (20 ton.ha-1) of guano fertilizer gave the best results at 30.38 gram pod weight and 2.27 ton.ha-1 bean production.